2000
DOI: 10.1016/s0002-9440(10)64631-7
|View full text |Cite
|
Sign up to set email alerts
|

Restricted 12p Amplification and RAS Mutation in Human Germ Cell Tumors of the Adult Testis

Abstract: Human testicular germ-cell tumors of young adults (TGCTs), both seminomas and nonseminomas, are characterized by 12p overrepresentation, mostly as isochromosomes, of which the biological and clinical significance is still unclear. A limited number of TGCTs has been identified with an additional highlevel amplification of a restricted region of 12p including the K-RAS proto-oncogene. Here we show that the incidence of these restricted 12p amplifications is ϳ8% in primary TGCTs. Within a single cell formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 51 publications
7
80
0
Order By: Relevance
“…The transcription factor SOX5 is located at the center of the amplicon, a region consistently showing a less-amplified level than the flanking sequences in some of the TGCTs investigated. This result is in line with our previous observation that this gene is not overexpressed in TGCTs with a 12p amplification and is, therefore, not a prime candidate (Roelofs et al, 2000;Rodriguez et al, 2003). The only annotated gene mapped to the telomeric border of the amplicon is EKI1 (Zafarana et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The transcription factor SOX5 is located at the center of the amplicon, a region consistently showing a less-amplified level than the flanking sequences in some of the TGCTs investigated. This result is in line with our previous observation that this gene is not overexpressed in TGCTs with a 12p amplification and is, therefore, not a prime candidate (Roelofs et al, 2000;Rodriguez et al, 2003). The only annotated gene mapped to the telomeric border of the amplicon is EKI1 (Zafarana et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Data regarding the physical description of these amplicons as well as the SRO are summarized in Table 2. The borders of the amplicon, as previously determined by FISH on tissue sections (Mostert et al, 1998;Roelofs et al, 2000;Zafarana et al, 2002), were found to be fully in line with the data obtained by array CGH. Since 20 out of the 68 BACs map within the SRO, the array data also allowed a detailed analysis of the amplicon structure for each individual tumor.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations